2022
DOI: 10.3390/jcm11174939
|View full text |Cite
|
Sign up to set email alerts
|

Position of the Hyoid Bone and Dimension of Nasopharynx and Oropharynx after Occlusal Splint Therapy and Physiotherapy in Patients Diagnosed with Temporomandibular Disorders

Abstract: Background: The aim of the study was to assess the position of the hyoid bone, as well as the width of the nasopharynx and oropharynx after occlusal splint therapy combined with physiotherapy in patients diagnosed with temporomandibular disorders (TMD). Methods: This was a clinical trial study. The study group consisted of 40 patients diagnosed with TMD, who were qualified for the treatment combining physiotherapy and occlusal splint therapy. Hyoid bone position as well as the width of the nasopharynx and orop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The study by Di Giacomo et al [25] revealed that dynamic splint therapy was more effective than stabilization splint therapy in increasing maximum jaw opening, reducing pain, and improving functional movements in patients with acute anterior disc displacement without reduction; this is likely due to its greater orthopedic action and joint mobilization. Derwich and Pawlowska [26] found that long-term occlusal splint therapy combined with physiotherapy significantly lowered the position of the hyoid bone and decreased the dimension of the lower part of the oropharynx in patients diagnosed with temporomandibular disorders. In their study, Sikora et al [27] demonstrated that repeated intra-articular injections of platelet-rich plasma (PRP) into temporomandibular joint (TMJ) cavities effectively reduced joint pain and increased mandibular mobility in patients with TMJ disorders, suggesting that PRP injections are a viable, minimally invasive treatment option for such conditions.…”
mentioning
confidence: 99%
“…The study by Di Giacomo et al [25] revealed that dynamic splint therapy was more effective than stabilization splint therapy in increasing maximum jaw opening, reducing pain, and improving functional movements in patients with acute anterior disc displacement without reduction; this is likely due to its greater orthopedic action and joint mobilization. Derwich and Pawlowska [26] found that long-term occlusal splint therapy combined with physiotherapy significantly lowered the position of the hyoid bone and decreased the dimension of the lower part of the oropharynx in patients diagnosed with temporomandibular disorders. In their study, Sikora et al [27] demonstrated that repeated intra-articular injections of platelet-rich plasma (PRP) into temporomandibular joint (TMJ) cavities effectively reduced joint pain and increased mandibular mobility in patients with TMJ disorders, suggesting that PRP injections are a viable, minimally invasive treatment option for such conditions.…”
mentioning
confidence: 99%